Spatial assessment of multi-hazard potential across scales using the social, ecological, and technological systems framework - Justin Huber; Heejun Chang (Natural Hazards, 2026)

Lyophilization of pharmaceuticals: an overview and practical approaches for developing the lyophilization cycle - Seon-Kwang Lee; Eun-Sol Ha; Heejun Park; Ji-Su Jeong; Chang Yell Shin; Jeong-Soo Kim; Seong Hoon Jeong; Min-Soo Kim (Journal of Pharmaceutical Investigation, 2026)

Watershed management may overcome effects of climate change on stream water quality in the Portland metropolitan area - Jason Sauer; Heejun Chang (Journal of Environmental Management, 2025)

Effects of climate change on stream temperature and salmonid habitats in a Cascades river basin - Michael Krochta; Kara Anlauf-Dunn; Dave Bugni; Heejun Chang (Journal of Environmental Management, 2025)

Effect of fracture characteristics on groundwater flow adjacent to high-level radioactive waste repository - Won Woo Yoon; Weon Shik Han; Jeonghwan Hwang; Jung-Woo Kim; Kyung Won Chang; Heejun Suk (Journal of Hydrology, 2024)

Relating social, ecological, and technological vulnerability to future flood exposure at two spatial scales in four U.S. cities - Jason Sauer; Arun Pallathadka; Idowu Ajibade; Marta Berbés-Blázquez; Heejun Chang; Elizabeth M. Cook; Nancy B. Grimm; David M. Iwaniec; Robert Lloyd; Gregory C. Post (Sustainable Cities and Society, 2023)

Effects of landscape characteristics, anthropogenic factors, and seasonality on water quality in Portland, Oregon - Katherine Gelsey; Heejun Chang; Daniel Ramirez (Environmental Monitoring and Assessment, 2023)

Transition of water quality policies in Oregon, USA and South Korea: a historical socio-hydrological approach - Hojeong Kim; Eugene Foster; Heejun Chang (Hydrological Sciences Journal, 2021)

Modeling the system dynamics of irrigators’ resilience to climate change in a glacier-influenced watershed - Alexander Reid Ross; Heejun Chang (Hydrological Sciences Journal, 2021)

Corrigendum: Use of Synthetic Salmon GnRH and Domperidone (Ovaprim®) in Sharks: Preparation for ex situ Conservation - Sang Wha Kim; Won Hee Hong; Se Jin Han; Jun Kwon; Heejun Ko; Sung Bin Lee; Sib Sankar Giri; Sang Guen Kim; Byung Yeop Kim; Goo Jang; Byeong Chun Lee; Dong Wan Kim; et al. (Frontiers in Marine Science, 2021)

Use of Synthetic Salmon GnRH and Domperidone (Ovaprim®) in Sharks: Preparation for ex situ Conservation - Sang Wha Kim; Won Hee Hong; Se Jin Han; Jun Kwon; Heejun Ko; Sung Bin Lee; Sib Sankar Giri; Sang Guen Kim; Byung Yeop Kim; Goo Jang; Byeong Chun Lee; Dong Wan Kim; et al. (Frontiers in Marine Science, 2020)
Shark populations are constantly decreasing owing to environmental destruction and overfishing; thus, sharks are now at a risk of extinction, with 27.9% of shark species classified as endangered on the International Union for Conservation of Nature’s Red List. Sharks are apex predators and a keystone species in balancing the marine food chain; their extinction will create an imbalance of the entire marine ecosystem. Assisted reproductive technology is the last resort for protecting animals facing severe extinction. Here, as a proactive effort toward building a hormone-induced artificial insemination protocol for endangered wild sharks, we identified the possibility of germ cell maturation by administration of Ovaprim ® , a commercially produced synthetic salmon gonadotropin-releasing hormone, and calculated its optimum dosage and injection timing. The experiment was conducted on two shark species— Triakis scyllium and Triaenodon obesus . We found that intramuscular injections of 0.2 mL/kg of Ovaprim ® for male T. scyllium and T. obesus , 0.2 mL/kg + 0.5 mL/kg at a 24 h interval for female T. scyllium , and 0.2 mL/kg + 0.2 mL/kg or 0.2 mL/kg + 0.3 mL/kg at a 24 h interval for female T. obesus were optimal dose protocols. These doses effectively induced the maturation and ovulation of oocytes and the release of semen. Our results confirm that Ovaprim ® is a suitable tool for shark hormone-induced artificial insemination and indicate that this method may enable the conservation of the endangered shark species.

Socio-hydrology with hydrosocial theory: two sides of the same coin? - Alexander Ross; Heejun Chang (Hydrological Sciences Journal, 2020)

Correction to: A community‑engaged approach to transdisciplinary doctoral training in urban ecosystem services - Heejun Chang; Elise F. Granek; David Ervin; Alan Yeakley; Veronica Dujon; Vivek Shandas (Sustainability Science, 2020)

A community-engaged approach to transdisciplinary doctoral training in urban ecosystem services - Heejun Chang; Elise F. Granek; David Ervin; Alan Yeakley; Veronica Dujon; Vivek Shandas (Sustainability Science, 2020)

Relation Between Stream Temperature and Landscape Characteristics Using Distance Weighted Metrics - Eric Craig Watson; Heejun Chang (Water Resources Management, 2018)

Recent research approaches to urban flood vulnerability, 2006–2016 - Seong Yun Cho; Heejun Chang (Natural Hazards, 2017)

Space and time dynamics of urban water demand in Portland, Oregon and Phoenix, Arizona - Seung-Jae Lee; Heejun Chang; Patricia Gober (Stochastic Environmental Research and Risk Assessment, 2015)

Vulnerability of Water Systems to the Effects of Climate Change and Urbanization: A Comparison of Phoenix, Arizona and Portland, Oregon (USA) - Kelli L. Larson; Colin Polsky; Patricia Gober; Heejun Chang; Vivek Shandas (Environmental Management, 2013)

Land cover, climate, and the summer surface energy balance in Phoenix, AZ, and Portland, OR - Ariane Middel; Anthony J. Brazel; Patricia Gober; Soe W. Myint; Heejun Chang; Jiunn‐Der Duh (International Journal of Climatology, 2012)
Changes in land use and land cover alter the local energy balance and contribute to distinct urban climates. This paper presents a local‐scale above‐canopy study of intra‐urban land cover mixes in two cities to analyse the relative effects of surface morphology and local climate on the surface energy balance (SEB). The study is conducted for urban areas in Phoenix, Arizona, and Portland, Oregon, cities with distinct climates but similarly warm and dry summers. A Local‐Scale Urban Meteorological Parameterization Scheme (LUMPS) is used to analyse the relative contributions of local weather extremes and land cover variations on the urban energy balance. The partitioning of net all‐wave radiation into turbulent sensible and latent heat fluxes as well as heat storage is investigated for a typical dry summer month and two extreme weather scenarios in the two cities. Results of sensitivity analyses show that incoming solar radiation is an important driver of the SEB in LUMPS and should be considered in the generation of climate scenarios. The relationship between individual land cover fractions and SEB fluxes is not clear because of interrelated effects of surface characteristics in the land cover mix. Daytime Bowen ratios vary inversely with vegetation fraction between and within cities for all weather scenarios. Impervious surface cover is positively correlated to the available energy that is partitioned into sensible heat. Cumulative evapotranspiration (ET) is similar for average weather conditions across medium wet sites in Phoenix and Portland but varies more in Portland than in Phoenix under extreme weather conditions. Results suggest that land cover manipulation could offset influences of weather extremes on ET in Portland to a certain degree but not in Phoenix. These findings highlight the importance of spatial and climatic context in the urban design process to mitigate the effects of urbanization. Copyright © 2011 Royal Meteorological Society

Climate change impacts on spatial patterns in drought risk in the Willamette River Basin, Oregon, USA - Il Won Jung; Heejun Chang (Theoretical and Applied Climatology, 2012)

Hydroclimatological response to dynamically downscaled climate change simulations for Korean basins - Eun-Soon Im; Il-Won Jung; Heejun Chang; Deg-Hyo Bae; Won-Tae Kwon (Climatic Change, 2010)

Winter precipitation intensity and ENSO/PDO variability in the Willamette Valley of Oregon - Sarah Praskievicz; Heejun Chang (International Journal of Climatology, 2009)
There is growing concern about the effects of inter‐annual climatic variability, such as the El‐Niño Southern Oscillation (ENSO) and the Pacific Decadal Oscillation (PDO), on regional hydrology and water resources. We analysed patterns of wintertime precipitation intensity, using both simple intensity and number of heavy precipitation days per year, for eight stations in northwestern Oregon's Willamette Valley for the period 1972–2006, and examined the separate and combined influence of ENSO and PDO on precipitation intensity. The analysis was accomplished using Kendall's tau and analysis of variance (ANOVA) to determine differences in precipitation intensity among combinations of positive and negative ENSO and PDO phases. The results suggest that the relation between ENSO phase and precipitation intensity is negative in November and positive in April, while the relation between PDO and intensity is negative and strongest in January and March. These varying seasonal associations with ENSO/PDO phase may be related to the Willamette Valley's location in the transitional zone between positive and negative El Niño response and to the moderating effects of out‐of‐phase ENSO/PDO. This seasonal variability of heavy rainfall has implications for the quantity and quality of regional water resources. Copyright © 2009 Royal Meteorological Society

Spatial Analysis of Water Use in Oregon, USA, 1985–2005 - Jon Franczyk; Heejun Chang (Water Resources Management, 2009)

What is responsible for increasing flood risks? The case of Gangwon Province, Korea - Heejun Chang; Jon Franczyk; Changhwan Kim (Natural Hazards, 2009)

Water quality during winter storm events in Spring Creek, Pennsylvania USA - Heejun Chang; Toby N. Carlson (Hydrobiologia, 2005)

Spatial and Temporal Variations of Water Quality in the Han River and Its Tributaries, Seoul, Korea, 1993–2002 - Heejun Chang (Water, Air, & Soil Pollution, 2005)